Inhibition of RIPK1-dependent regulated acinar cell necrosis provides protection against acute pancreatitis via the RIPK1/NF-κB/AQP8 pathway - Peng-yu Duan; Yuan Ma; Xi-na Li; Feng-zhi Qu; Liang Ji; Xiao-yu Guo; Wang-jun Zhang; Fan Xiao; Le Li; Ji-sheng Hu; Bei Sun; Gang Wang (Experimental and Molecular Medicine)
Abstract Currently, preliminary results have confirmed the existence of receptor-interacting protein kinase 3 (RIPK3) and mixed lineage kinase domain-like protein (MLKL)-dependent necroptosis of pancreatic acinar cells during early acute pancreatitis (AP), which might be a potential target for the effective regulation of necroinflammatory injury. However, the exact effect of receptor-interacting protein kinase 1 (RIPK1)-dependent regulated acinar cell necrosis on AP is still uncertain. In our study, we first explored the changes in the degree of local and systemic inflammation in AP rats when the activation of acinar cell RIPK1 was inhibited. The RIPK1 inhibitor Nec-1 was used to treat rats, and the levels of related inflammatory markers, necrosis indicators and apoptotic indicators were measured. Changes in pancreatic nuclear factor κB (NF-κB) and aquaporin 8 (AQP8) expression were noted. Next, the expression of AQP8 in AR42J cells was inhibited, and the degree of cell necrosis and inflammatory damage was found to be significantly reduced. Most importantly, we demonstrated that the RIPK1/NF-ĸB/AQP8 axis might be a potential regulatory pathway mediating RIPK1-dependent regulated acinar cell necrosis in early AP. Finally, we used the NF-κB inhibitor PDTC and Nec-1 to treat rats in different groups and measured the degree of pathological pancreatic injury, the activation of RIPK1, and the expression of NF-κB and AQP8. In summary, we hypothesized that there might be a RIPK1/NF-ĸB/AQP8 pathway controlling RIPK1-dependent regulated necrosis of acinar cells in AP, which might be a promising therapeutic target against AP-related injury.